The Effectiveness of plastic jersey barriers on work zone control during road construction / Muhammad Hakim Mohd Radin - Muhammad Hakim, Mohd Radin (2019)
Plastic jersey barriers have been frequently used during road constructions or during road maintenance works. The purpose of this study is to highlight the functions of plastic jersey barriers, the effectiveness of plastic jersey barriers and ways to solve the issues of the ineffectiveness of using plastic jersey barriers during road construction. Following that, this research focuses on the effectiveness of plastic jersey barriers during road construction. To achieve the objectives of this study a questionnaire survey is conducted to obtain the required data. The questionnaire was derived from a review of the literature. Detailed and efficient research is required to examine the ways to solve the issue of the effectiveness of using plastic jersey barriers during road construction. The data is collected from ninety (90) respondents, which are civil contractors (G7) who are engaged in various types of civil and infrastructure projects in Malaysia. This scope of this study is focused on the effectiveness of using plastic traffic barriers in road constructions in Kelantan. This is because there are many problems with plastic traffic barriers that arising during road construction in Kelantan mostly at Kota Bharu area. The data has been analysed using Microsoft Word 2016, Microsoft Excel 2016 and Statistical Packaging for Social Science (SPSS) software and is interpreted in the form of table and bar chart and was ranked according to the mean score range. The data analysis and findings concluded that the plastic jersey barriers were used to separate the work area and the travelled way during construction. In addition, the plastic jersey barriers were most effective when located near the road construction area rather than installed in the work zone control. With regard to the way to solve the issue of the ineffectiveness of plastic jersey barriers during road construction is by improving the lighting system on the plastic jersey barriers and near the road construction area because the main issue of plastic jersey barriers is its poor lighting system especially at night, dusk and rainy days. All parties with the full support of the Malaysia government should play their major roles by making sure that they practice an appropriate and safe working attitude to minimize the accident rates in the construction site. The result obtained is to provide some insights for further work.